ANALYSIS OF THE ROLE OF GOOD HUMAN RELATIONS AND INTERPERSONAL COMMUNICATION ON EMPLOYEE PERFORMANCE AT THE SIBOLGA CITY INSPECTORATE OFFICE - Fauziah Nur Simamora (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
The purpose of this study was to determine the relationship between interpersonal communication and good human relations on the performance of employees at the Sibolga City Inspectorate Office. The method used in this study is a quantitative descriptive method, while the analysis method used in this study is multiple linear regression, the sample of this study amounted to 58 people, sampling using saturated sampling technique, namely a sampling technique where the entire population is sampled. Data analysis using multiple linear regression tests, hypothesis testing using the coefficient of determination test (R2) and the partial test (t test) while data processing using SPSS 26. The results of this study indicate that the variables of interpersonal communication and good human relations affect the performance of employees at the Sibolga City Inspectorate Office. It is shown by the results of the reliability test of the interpersonal communication variable (X1) which has a tcount value (4.164)> ttable value (1.983). The variable good human relations (X2) has a tcount value (9.989) > ttable value (1.983) the results of the determination coefficient test in the table above can be understood that the R-Square value of 0.759 in the regression model is 75.9%. Based on the results of the study, it can be concluded that interpersonal communication good human relations are two determining factors that greatly affect individual and organizational performance such as in the Sibolga City Inspectorate Office. Interpersonal communication has an important role in improving employee performance in addition, good employee relations will create high employee loyalty and retention and create a positive and inclusive work culture where each employee will feel safe, fair and appreciated.